Increasing Student Engagement through Authentic Learning Activities in MOOC Environment E-learning - Syahrul Nizam, Bin Junaini; Johari, Bin Abdullah; Yanti Rosmunie, Binti Bujang; Ahmad Hadinata, Bin Fauzi; Jonathan, Sidi (Academic Enhancement and Leadership Development Centre (ADeC), Universiti Malaya, 2019)
Learner engagement is one of the most principal factor that determines the effectiveness on ‎MOOC. From the study, we found that most of the students gave positive comments especially on ‎the learning activities. Overall, positive comments were received especially in terms of active ‎interaction from the instructor.‎